Pengembangan Traditional Game Congklak pada Materi Penjumlahan dan Pengurangan untuk Meningkatkan Kemampuan Berhitung Siswa Kelas 1 - maysaroh, siti; Cindya Alfi; Mohamad Fatih (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research originates from the results of preliminary observations and interviews conducted with elementary school teachers at SDIT Al-Firdaus Semen. The learning process was found to be problematic, due to a lack of various teaching materials. The limited variety of media results in a lack of engagement among students, leading to boredom and distraction during arithmetic lessons. Students often stray off course, engaging in conversations with peers or immersing themselves in other activities in the classroom. To answer this problem, the traditional congklak game was introduced as a pedagogical tool to improve the numeracy skills of first grade students at SDIT Al-Firdaus Semen. Using the ADDIE research model, this study involved a total of 15 participants. The Research and Development method or commonly referred to as RnD is guided by the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The tools used in this process include material expert sheets, media experts, user experts (teachers), as well as pretest and posttest assessments. The purpose of this study was to improve the numeracy skills of first grade students at SDIT Al-Firdaus in addition and subtraction. The results showed that media experts rated the results of the assessment at 82.5% (very feasible), material experts at 90% (very feasible), and user experts (teachers) at 100% (very feasible). Together, these assessments show that the traditional congklak game media is very suitable for improving the arithmetic addition and subtraction skills of grade 1 SDIT Al-Firdaus students. Congklak Traditional Game Media not only improves students' numeracy skills but also provides valuable data through pretest and posttest scores which are then calculated using N-Gain. The average N-Gain value obtained is 81.38%, indicating a high level of improvement. Based on this, it can be concluded that the use of Congklak Traditional Game media is highly recommended and effective in improving students' numeracy skills.